Arginine methyltransferase PRMT5 methylates and destabilizes Mxi1 to confer radioresistance in non-small cell lung cancer. (28th April 2022) - Yang, Xijie; Zeng, Zhen; Jie, Xiaohua; Wang, Ye; Han, Jun; Zheng, Zhikun; Li, Jinsong; Liu, Hongli; Dong, Xiaorong; Wu, Gang; Xu, Shuangbing
Abstract: Radioresistance is regarded as the main cause of local recurrence and distant metastasis in non-small cell lung cancer. However, the underlying mechanisms of radioresistance remains incompletely understood. In this study, we find that the arginine methyltransferase PRMT5 interacts with and methylates Mxi1, which promotes the binding of the β-Trcp ligase to Mxi1, facilitating the ubiquitination and degradation of Mxi1 in lung cancer. Furthermore, genetic blockade of PRMT5 impairs DNA damage repair and enhances lung cancer radiosensitivity in vitro and in vivo, and these phenotypes are partially reversed by Mxi1 silencing. More importantly, pharmacological inhibition of PRMT5 with the specific inhibitor EPZ015666 leads to extraordinary radiosensitization in vitro and in vivo in lung cancer. Altogether, our data indicate that PRMT5 methylates and destabilizes Mxi1 to confer radioresistance, suggesting that PRMT5 may be a promising radiosensitization target in non-small cell lung cancer. Highlights: PRMT5 interacts with and methylates Mxi1 in vitro and in vivo. The methylation of Mxi1 by PRMT5 facilitates the ubiquitination and degradation of Mxi1. Inhibition of PRMT5 exhibites a radiosensitization effect in non-small cell lung cancer in vitro and in vivo. PRMT5 participates in lung cancer radioresistance in a Mxi1-dependent manner.